The evolution of currency systems: from the gold standard to digital currencies ("Journal "U". Economy. Management. Finance.", 2025)
The article examines the evolution of currency systems. Examining the history of the development of currency systems, it can be noted that the gold and foreign exchange standard, which had previously ensured stability, was replaced by more flexible systems, which, in turn, made it possible to adapt to changing economic conditions. To date, interest in digital currencies has increased, for example, cryptocurrency, which are already beginning to change global financial flows. The identification and analysis of key stages in the evolution of the global monetary system allows us to identify and assess the prospects for further development of the system in the context of technological changes and geopolitical instability.
Keywords: monetary system; digital currencies; Bretton Woods system; Jamaican system; Post-Jamaican monetary system; financial crisis